Polo de educação a distância de Alegre e a formação de professores na região do Caparaó – ES - Chaves, Lizzie de Almeida (2020)
Recent research shows that distance education has been expanding rapidly in higher education in Brazil. In this context, a case study was carried out in order to analyze the possible contributions or challenges faced by licentiate degree courses offered i